Penerapan Model Pembelajaran Small Group Discussion Dalam Meningkatkan Hasil Belajar Siswa Materi Keutuhan Negera Kesatuan Republik Indonesia Di Kelas V SD Negeri 1 Poka - Yudith Hukunala; Samuel P Ritiaw; Lisye Salamor (Teacher Training and Education Faculty, Widya Gama Mahakam Samarinda University, 2025)
This study aims to determine the application of the Small Group Discussion learning model in improving student learning outcomes and learning activities in the subject of Citizenship Education (PKn) on the material of the Unitary State of the Republic of Indonesia in grade V of SD Negeri 1 Poka. The type of research used is Classroom Action Research (CAR) with quantitative and qualitative approaches implemented in two cycles. The subjects of the study were 20 students of grade V of SD Negeri 1 Poka. Data collection techniques used include observation, tests, interviews, and documentation. Data were analyzed using quantitative and qualitative descriptive analysis. The results of the study indicate that the application of the Small Group Discussion model can improve student learning activities as indicated by increased student participation in group discussions and active involvement in the learning process. In addition, student learning outcomes also increased, where in Cycle II the number of students who achieved the Minimum Completion Criteria (KKM) ≥ 64 has fulfilled the research success indicators, namely at least 64% of students achieved learning completion. Thus, it can be concluded that the implementation of the Small Group Discussion learning model is effective in improving student activity and learning outcomes in Civics learning on the topic of the Unitary State of the Republic of Indonesia in fifth grade at SD Negeri 1 Poka.